Climatological analysis of the optical properties of aerosols and their direct radiative forcing in the Middle East. (February 2019) - Gharibzadeh, Maryam; Alam, Khan; Abedini, Yousefali; Bidokhti, Abbasali Aliakbari; Masoumi, Amir; Bibi, Humera; Zeb, Bahadar
Abstract: In addition to climate perturbations, various problems such as air pollution, reduction in the visibility and human health hazards were caused by atmospheric aerosols in the Middle East specifically in the last two decades. With the help of the Aerosol Robotic NETwork (AERONET), the measurement of the aerosol optical and radiative properties were carried out over seven sites in the Middle East during 2013. The analysis of the optical properties of aerosols like Single Scattering Albedo (SSA), Angstrom Exponent (AE), Aerosol Optical Depth (AOD), and Asymmetry parameter (ASY) were carried out during the study period. During spring and summer, high values of AOD and low values of AE were found in all sites except CUT-TEPAK (Limassol, Cyprus), which specified the existence of coarse mode particles and dust storms in these seasons. The AE maximum values were found in the summer and fall over CUT-TEPAK and IMS-METU-ERDEMLI(Erdemli, Turkey), whereas in other sites IASBS (Zanjan, Iran), KAUST Campus (Thuwal, Saudi Arabia), Masdar Institute (Masdar, United Arab Emirates), Mezaira (Mezaira, United Arab Emirates) and Solar Village (Riyadh, Saudi Arabia) the peak values of AE occurred in the fall and winter. The maximum values of SSA and ASY were observed in the spring and summer over all sites except over CUT-TEPAK and IMS-METU-ERDEMLI. The Santa Barbara DISORT Atmospheric Radiative Transfer (SBDART) model has been used for the calculations of the Aerosol Radiative Forcing (ARF) over the selected sites. We obtained negative value of ARF at the surface, which suggesting its cooling effects because of the loss of radiation back to space due to aerosols. The averaged ARF values at the SuRFace (SRF) of the earth were −43.8 Wm -2, -31 Wm -2, -56.8 Wm -2, -61.7 Wm -2, -52.5 Wm -2, -54.9 Wm -2, and -72.2 Wm -2, over CUT-TEPAK, IASABS, IMS-METU-ERDEMLI, KAUST Campus, Masdar Institute, Mezaira and Solar Village, respectively. While the positive value of atmospheric ARF showed heating of the atmosphere. Highlights: Aerosol optical & radiative properties have analyzed in the Middle East. High AOD & low alpha values showed the existence of dust during spring & summer. SSA & ASY suggested predominant of coarse particles during spring & summer. Aerosol Radiative Forcing reveal significant heating in the atmosphere. The AERONET-SBDART correlation is greater than 0.94 over all sites.